2021
DOI: 10.3389/fcell.2020.592442
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 (CD90)-Induced Metastatic Cancer Cell Migration and Invasion Are β3 Integrin-Dependent and Involve a Ca2+/P2X7 Receptor Signaling Axis

Abstract: Cancer cell adhesion to the vascular endothelium is an important step in tumor metastasis. Thy-1 (CD90), a cell adhesion molecule expressed in activated endothelial cells, has been implicated in melanoma metastasis by binding to integrins present in cancer cells. However, the signaling pathway(s) triggered by this Thy-1-Integrin interaction in cancer cells remains to be defined. Our previously reported data indicate that Ca2+-dependent hemichannel opening, as well as the P2X7 receptor, are key players in Thy-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Our laboratory has described a role for Thy-1 in integrin ligation. Upon binding to integrins, Thy-1 increases integrin expression and clustering, focal adhesion and stress fiber formation, as well as cell contractility and migration of astrocytes ( Avalos et al, 2004 ; Lagos-Cabré et al, 2017 , 2018 ) and cancer cells ( Brenet et al, 2020 ). Mechanical tension generated by a stiffer ECM also drives clustering of integrins ( Cluzel et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has described a role for Thy-1 in integrin ligation. Upon binding to integrins, Thy-1 increases integrin expression and clustering, focal adhesion and stress fiber formation, as well as cell contractility and migration of astrocytes ( Avalos et al, 2004 ; Lagos-Cabré et al, 2017 , 2018 ) and cancer cells ( Brenet et al, 2020 ). Mechanical tension generated by a stiffer ECM also drives clustering of integrins ( Cluzel et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD90 was reported as a stem cell marker that had an association with a number of cell surface molecules that allow the formation of extra/intracellular multiprotein complexes that could promote cancer formation in various cancer cell lines [ 21 , 22 , 23 ]. CD90-α V β 3 integrin interaction is important for cancer cell migration, invasion, and transvasation [ 24 ]. β3 integrin was also reported to be required for the promotion of sphere formation and up-regulated the expression of the cancer stem cell marker CD133 by CD90 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pioneer studies that revealed PANX1 interaction with the actin cytoskeleton, suggested its pro-migratory phenotype in breast cancer ( 25 ). Indeed, PANX1 promotes motility, transmigration, and in vivo invasion in melanoma, breast and testicular cancer cells: B16-BL6, B16-F10; CN34, CN-LM1A, MDA-MB-231 MDA-MB-468, MDA-LM2, and I-10 cells, respectively ( 99 , 100 , 122 , 123 ). In some cases, such as testicular cancer PANX1 activity was required for ERK1/2 activity, E-cadherin and metalloproteinase 9 (MMP-9) revealing that these channels contribute with different aspects of cell migration ( 99 ).…”
Section: Role Of Panxs On Migration Of Non-immune Cellsmentioning
confidence: 99%
“…Like normal fibroblasts (see section above), MDA-MB-231 cells are sensitive to Thy-1 that increases cell migration by releasing ATP via PANX1 channels with subsequent activation of P2X 7 receptors in a positive feedback loop ( 123 ). Consequently, a mutation that increases the permeability of PANX1 channels leading to an exacerbated ATP release, also promotes cell motility, but not trans-endothelial migration ( 100 ), suggesting that PANX1 contributes to specific steps during tumor progression.…”
Section: Role Of Panxs On Migration Of Non-immune Cellsmentioning
confidence: 99%